The Effectiveness of Regulation in Improving the Fishing Port Services - Dirman, Eris Nur; Riniwati, Harsuko; Harahab, Nuddin; Semedi, Bambang; Rachmansyah, Arief (Jurnal Pembangunan dan Alam Lestari, 2024)
Indonesia is a maritime nation with a potential economy in the fishing sector. However, the sustainability of Indonesia's fishing sector is facing many challenges, such as overfishing, illegal fishing activities, and the degradation of marine habitats. The fishing ports play a significant role in overcoming these challenges. Therefore, the government has developed several regulations to ensure the fisheries ports provide a safe and efficient way for fishing activities, an economic center for many coastal communities, and sustainable fishing operations. There is a need to assess the effectiveness of these regulations; hence, this research aims to analyze the effectiveness of regulation in improving the services in the fishing ports. The method of stratified random sampling in proportion was conducted to select 291 participants of administrative offices, fishing companies, and fisherman organizations from 6 fishing ports in east Java Province. This research used structural equation modeling (SEM) as a comprehensive approach to assessing the effectiveness of regulation in fishing ports. The result found that the regulation variable has a significant relationship with port services that = 5.099 (p<0,001). The analysis showed that the regulation variable indirectly affects the port services variable through infrastructure, economy, and social community variables (p<0,001). Furthermore, the result recommended that the regulation will enhance port services by improving the physical infrastructure of the port, boosting the local economy, and benefiting the social community. These findings have significant implications for the fishing industry, as they demonstrate the potential for regulations to improve the efficiency and sustainability of fishing port services. Keywords: Effective, Fishing port, Regulation, Structural equation modeling, Port services